On income tax avoidance - the case of Germany revisited - Hannes Fauser (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
I study tax avoidance along the income distribution based on micro data from the Income and Consumption Survey (EVS) for the year 2013. The richness of the survey concerning income, taxes and expenditures is exploited by modelling the German tax code in terms of the items available in the EVS. I.e, components of taxable income and deductions are estimated as precisely as possible in a microsimulation model. Results confirm findings in the literature claiming that tax avoidance increases with rising income. The estimated amount of avoided tax is largest for the richest decile of individual tax payers, at around 3.1% of taxable income before deductions or 17.2% of taxes paid. Expectedly at the household level, the amount avoided by the highest income decile is reduced somewhat, to 2.1% of taxable income before deductions or 11.2% of taxes paid. Aggregate losses at the national amount to at least EUR 12.4 bn, or 5.0% of assessed income tax revenues.
Keywords: D12; D31; D63; H26; 330; tax compliance; tax avoidance; income taxation; microsimulation; distributional effects